Weakness and the Inability to Ambulate in a 14-Month-Old Female: A Case Report and Concise Review of Guillain-Barre Syndrome. (30th January 2013) - Bloch, Scott A.; Akhavan, Mahsa; Avarello, Jahn
Abstract : Guillain-Barre syndrome (GBS) is an acquired disease of the peripheral nervous system which causes demyelination and leads to weakness, ataxia, and areflexia. There are a variety of forms of the syndrome, and although it is found in all age groups, it is rare in children less than two years of age. The present complaint of weakness, ataxia, or lower extremity pain in the pediatric population should cause the practitioner to consider GBS in the differential. We describe a case of a 14-month-old girl presenting with weakness and the inability to ambulate who was diagnosed with GBS. The purpose of this paper is to review the emergency medicine diagnosis and management of Guillain-Barre syndrome in children.